The Development of Students’ Cognitive Self-Study While Teaching Reading in FL Training - Andrianova, Natalia S.; Nizamieva, Liliya R.; Nazarova, Gulnara I.; Ostroumova, Olga F.; Leblanc, Cecile (Journal of History Culture and Art Research, 2017)
In the informational society while teaching foreign languages the development of students’ skills aimed at searching, analyzing, critical thinking, processing and using the obtained information in the productive speech activity is in demand. In this context, the problem of students’ cognitive self-study development, aimed at “revealing” knowledge while reading, is becoming increasingly important as reading while teaching foreign languages not only contributes to self-development and self-reflection, but also to the formation of a cross-cultural and linguistic personality, which is a priority of linguistic education. The solution of the above-mentioned problems has defined the aim of our research: it is the development and implementation of technologies for optimizing students’ self-study in teaching reading. In the course of our experimental work the implementation of the principle of multi-level approach in the form of five interrelated elements in teaching reading – from the level of mastering reading techniques to the level of critical reading and stylistic comprehension reading – contributed to the ultimate development and improvement of students’ constructive-creative self-study. During the experimental work while testing the effectiveness of our methods of cognitive-practical activities, we concluded that in the process of teaching foreign languages, these methods are an effective way of teaching reading, activating students’ self-study, forming linguistic creativity, which manifests itself in the ability to produce oral and written discourses based on the creative potential development of a linguistic personality. The results obtained in the experiment can be used in educational process while creating and implementing the algorithm of organizing students’ self-study while teaching foreign languages.